The Effect of Interactive Multimedia Wordwall on Students’ Vocabulary Learning Outcomes at SMA Negeri 1 Huruna - Gulo Prima Belvin; Afore Tahir Harefa; Yasminar Amaerita Telaumbanua; Riswan Zega (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2024)
Vocabulary learning is an essential component in mastering reading skills, which directly impacts students' ability to communicate effectively in both oral and written forms. However, many students at SMA Negeri 1 Huruna experience difficulties and lack motivation in the vocabulary learning process. This study to explore and examine the effectiveness of using interactive multimedia based on the Wordwall application in improving students' vocabulary learning outcomes. The research employs a quasi-experimental method with a pre-test and post-test design. The subjects of the study consist of students at SMA Negeri 1 Huruna, the population were all tenth-grade students which 60 students, divided into two groups as a sample: an experimental group that uses the Wordwall application as 30 students and a control group that apply conventional teaching methods as 30 students. The results of the analysis indicate a significant increase in the vocabulary learning outcomes of students taught using the Wordwall application compared to those in the control group. The mean pre-test score for the experimental group was 35.50, while the post-test mean increased to 89.13. In contrast, the control group showed a smaller increase, with a pre-test mean of 33.53 and a post-test average of 74. These findings demonstrate that the Wordwall application not only makes learning more engaging but also enhances students' understanding of the vocabulary taught. Students involved in Wordwall-based learning exhibited higher enthusiasm and were able to participate actively in class activities. Overall, these findings provide valuable insights for educators regarding the importance of technology integration in teaching and encourage the development of more innovative and responsive teaching methods that meet students' needs.